Debunking rumors on social media : the use of denials - Pal, Anjan (2021)
The literature currently lacks an understanding of how denials can be crafted to effectively debunk rumors on social media. Underpinned by the theory of planned behavior, this research develops denials by incorporating salient beliefs to enhance users’ likelihood to share such messages. Two related studies were conducted. The first was a survey of 276 participants to identify salient beliefs that could be incorporated to develop rumor denials. The following salient beliefs were identified in the survey: (i) Sharing denials helps to spread the truth; (ii) Friends and the online community encourage the behavior of sharing denials; and (iii) Source credibility of denials encourages sharing. From among the pool of survey participants, 206 took part in a second study that employed an experiment to measure the efficacy of the developed denials. The experiment revealed that denials incorporating all the salient beliefs had the greatest potential to influence users’ likelihood of sharing. With a theory-driven approach to develop denials, this research offers insights to practitioners such as social media managers and website authorities on ways to debunk rumors.